Implementation of Exemplary Leadership in Character Building of Students at Ra As Syifa, Tarakan City - Rusdiani Salikunna Rusdiani Salikunna (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the implementation of exemplary leadership in developing student character at RA As-Syifa, Tarakan City, and to identify factors that support and hinder its effectiveness. The research used a qualitative approach with a case study method through observation, interviews, and documentation involving the RA principal, teachers, education staff, parents, and students. The results show that exemplary leadership is implemented through the concrete behavior of the madrasah principal and teachers, reflecting religious values, discipline, responsibility, honesty, social awareness, and polite communication. This exemplary leadership is manifested in the learning process, madrasah culture, daily habits, religious activities, and daily social interactions. The success of its implementation is supported by leadership commitment, a conducive organizational culture, collaboration between the madrasah and families, and the integration of Islamic values ​​into the curriculum. Meanwhile, inhibiting factors include the uncontrolled influence of digital media, differences in family parenting styles, limited time for teacher-student interaction, and challenges of the urban social environment. This research confirms that exemplary leadership is an effective strategy in shaping the character of early childhood learners if implemented consistently, collaboratively, and sustainably.